Climate Change and Armed Conflict in the Horn of Africa Region (International Journal of Scientific Research in Science and Technology, 2025)
The influence of environmental variability on pastoral conflict in the Horn of Africa cannot be underestimated. Studies on climate change and violent conflict in the Horn of Africa indicated that changing rainfall patterns, drought, changes in vegetation cover, and increasing resource scarcity have contributed to various types of violent conflict. Research also shows that these local resource conflicts are sometimes drawn into more intense power struggles related to civil war. In this paper, four interlinked mechanisms can be identified for why and when climate change increases the risk of violent conflict in the greater Horn of Africa: (a) worsening livelihood conditions; (b) migration and changing pastoral mobility patterns; (c) tactical considerations of armed groups; and (d) exploitation of local grievances by the elite. These mechanisms can be divided into two categories. The first two mainly relate to the causes of conflict, while the latter two mainly relate to changing conflict dynamics.